Supporting prostate cancer survivors in primary care: Findings from a pilot trial of a nurse-led psycho-educational intervention (PROSPECTIV). (February 2018) - Watson, Eila K.; Shinkins, Bethany; Matheson, Lauren; Burns, Richeal M.; Frith, Emma; Neal, David; Hamdy, Freddie; Walter, Fiona M.; Weller, David; Wilkinson, Claire; Faithfull, Sara; Sooriakumaran, Prasanna; et al.
Abstract: Purpose: This study sought to test the acceptability and feasibility of a nurse-led psycho-educational intervention (NLPI) delivered in primary care to prostate cancer survivors, and to provide preliminary estimates of the effectiveness of the intervention. Methods: Men who reported an ongoing problem with urinary, bowel, sexual or hormone-related functioning/vitality on a self-completion questionnaire were invited to participate. Participants were randomly assigned to the NLPI plus usual care, or to usual care alone. Recruitment and retention rates were assessed. Prostate-related quality of life, self-efficacy, unmet needs, and psychological morbidity were measured at baseline and 9 months. Health-care resource use data was also collected. An integrated qualitative study assessed experiences of the intervention. Results: 61% eligible men (83/136) participated in the trial, with an 87% (72/83) completion rate. Interviews indicated that the intervention filled an important gap in care following treatment completion, helping men to self-manage, and improving their sense of well-being. However, only a small reduction in unmet needs and small improvement in self-efficacy was observed, and no difference in prostate-related quality of life or psychological morbidity. Patients receiving the NLPI recorded more primary care visits, while the usual care group recorded more secondary care visits. Most men (70%; (21/30)) felt the optimal time for the intervention was around the time of diagnosis/before the end of treatment. Conclusions: Findings suggest a nurse-led psycho-educational intervention in primary care is feasible, acceptable and potentially useful to prostate cancer survivors. Highlights: Delivering a nurse-led intervention in primary care to support men with prostate cancer is feasible and acceptable. Men found the intervention useful, and it appeared to fill a gap in their care. Only small differences in patient outcome measures were found. A larger trial is needed to confirm intervention effectiveness. Participants were on average two years post-diagnosis – offering the intervention earlier may bring greater benefits.